Les méthodes « post-keynésiennes » et l’approche post-classique - Henry, Jacques (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe two most basic non-metaphysical materials used by economists to erect their theoretical structures are prices and quantifies. Two visions of reality are contrasted: (a) that in which historical price determination is explained without reference to demand (Sraffa), and (b) that in which the determination of quantities in historical time is explained without explicit reference to supply (Keynes). In the neoclassical vision of reality, prices and quantities are simultaneously determined by both demand and supply in logical time. It is then argued that the "post-keynesian" appellation is misleading. What is needed is a truly post-classical approach based on the works of Keynes, Sraffa and Marx.